3D printed acoustic metamaterial for noise reduction - Teo, Zue Kang (2018)
Noise pollution has always been a problem that situated in our daily lives especially area where unnecessary sound produces by traffic and Mass Rapid Transport (MRT) can cause irritation to the residents nearby. Helmholtz resonator is a largely use acoustic passive damper to help attenuate the acoustic pressure wave to a certain frequency for sound damping purposes. In this report the author will present a simulation study and design of a 3D printed sound reduction panel which make use of a modified Helmholtz resonator neck by embedding a coplanar spiral tube in place of a Helmholtz resonator neck which will help reduce the overall thickness of the Helmholtz resonator yet keeping the acoustic damping properties as a Helmholtz resonator. The sound transmission loss characteristic of a coplanar spiral tube Helmholtz resonator are first studied from a frequency range of 20 hz to 10 Khz with varying geometry such as the cavity volume, spiral cross-sectional dimensions and spiral length. Design of the prototype will then be experimented base on the transmission loss plot from the simulation data. Discussion of the simulation results, design of the sound reduction panel, drawings of the prototype are presented in this report.